Treatment of dilute wastewater with two-stage anaerobic fluidized bed membrane bioreactor - Mohamed Faris Nashir Bounaparte. (2012)
In recent years, the anaerobic treatment of municipal wastewater is gaining attractiveness over the aerobic treatment process because it consumes a lower amount of energy as no aeration is required, produces a lower volume of sludge, and generates methane gas that can be used as an alternative source of energy to lower operation costs in wastewater treatment plants. Anaerobic processes have been widely adopted in the treatment of high-strength wastewater, such as those from the chemical and food processing industries. However, when it comes to the treatment of dilute wastewater, there are several shortcomings, such as its low biomass yield requires a high biomass inventory, and also long hydraulic and solids retention times (SRT). Moreover, the effluent quality from this treatment is poorer than the aerobic process, thus making it insufficient in meeting stringent effluent requirements, in terms of chemical oxygen demand (COD) and suspended solids (SS). Various strategies have been developed in order to achieve long SRT in the reactor, such as anaerobic filter, anaerobic contact process, upflow anaerobic sludge blanket (UASB) reactor, expanded granular sludge bed (EGSB), anaerobic fluidized bed bioreactor (AFBR) and anaerobic sequencing batch reactor. The UASB and EGSB processes have been widely used. However, these systems require scrupulous process control to achieve and sustain sludge granulation. A strategy that has gained more interest is the utilization of the anaerobic fluidized bed membrane bioreactor (AFMBR), which is particularly beneficial because it is not as subject as most other reactor types to microorganism washout at short HRT and it has a good mass transfer characteristic. However, there is little knowledge in the utilization of a two-stage treatment process involving an AFBR coupled with a flat sheet AFMBR, both using granular activated carbon (GAC) as its support media. Thus, this report will discuss the performance of this particular two-stage AFMBR process for the treatment of dilute synthetic wastewater. From the experiment conducted, an average COD removal of 62% was achieved for the overall two-stage process. The methane generated was found to have an average of 2040 CH4/g VSS and 0.467 L CH4/g COD over a period of 46 days. EPS and SMP, particle size distribution and pH were also investigated in this experiment.